2015
DOI: 10.1007/s10661-015-4406-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of polycyclic aromatic hydrocarbons in surface sediments of lower reaches of the Don River (Russia) and their ecotoxicologic assessment by bacterial lux-biosensors

Abstract: The lower Don River in the south of the European part of Russia was studied to determine the concentration, spatial distribution, and sources of 19 polycyclic aromatic hydrocarbons (PAHs) in surface sediments. Total PAH concentrations ranged from 14.2 to 529 ng/g-dw. Sedimentary PAH concentrations were higher in the delta of the Don River and in the estuaries of rivers Sal and Aksai compared to the main channel of the Don. Analysis of the PAHs sources showed that PAHs came mostly from pyrogenic sources as a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…The bioavailability of pollutants, not just their direct concentration in environmental samples, is also important. This was shown by Sazykin et al [32] when studying the ecotoxicity of river Don bottom sediments using bacterial lux biosensors, as well as by Azhogina et al [18], who found a close connection between the response of biosensors and the concentration of bioavailable PAHs.…”
Section: Discussionmentioning
confidence: 68%
“…The bioavailability of pollutants, not just their direct concentration in environmental samples, is also important. This was shown by Sazykin et al [32] when studying the ecotoxicity of river Don bottom sediments using bacterial lux biosensors, as well as by Azhogina et al [18], who found a close connection between the response of biosensors and the concentration of bioavailable PAHs.…”
Section: Discussionmentioning
confidence: 68%
“…Кроме того, самые распространенные химические вещества не обязательно оказывают наибольшее биологическое воздействие на водные организмы. Важные данные для оценки экологических рисков, возникающих в водных экосистемах, можно получить с помощью биотестирования на основе цельноклеточных люминесцентных бактериальных сенсоров, которое дополняет химические анализы [4,5] Для приготовления экстрактов в колбу Эрленмейера вместимостью 50 мл вносили по 10 г исследуемых тканей рыб и 10 мл 1%-ного раствора TWEEN-80 (Amresco) в 96%-ном этаноле. Получившуюся суспензию помещали в шейкер-инкубатор Innova 40R (New Brunswick Scientifi c, США) и экстрагировали в течение 24 часов при температуре 30 °С и скорости вращения 250 оборотов в минуту.…”
Section: Introductionunclassified